2021
DOI: 10.1002/pc.26370
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative study of alkali treated date palm fiber based brake friction composites and standard Kevlar‐based brake friction composites

Abstract: Recently many research studies have revealed the increasing importance of natural fiber in modern applications. Natural fibers are used these days in many important sectors like medical, aerospace, agriculture, and so forth. The cause of increasing the application of natural fiber in different fields is its ecofriendly behavior and excellent mechanical properties. In the research work, date palm, a natural fiber, is used to replace asbestos and Kevlar, which are very harmful to the human body. There are very f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The hydrophilic ionic liquid introduced surface roughness and improved the hydrophilicity of polyacrylonitrile nanofibres. The interlinked nanofibrous structure and the surface chemistry of the nanofibrous membranes are responsible for the higher affinity of the nanofibres for PM2.5 and thus the PM2.5 capture increases for polyacrylonitrile/diethyl ammonium dihydrogen phosphate nanofibre in comparison with polyacrylonitrile nanofibrous membranes [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophilic ionic liquid introduced surface roughness and improved the hydrophilicity of polyacrylonitrile nanofibres. The interlinked nanofibrous structure and the surface chemistry of the nanofibrous membranes are responsible for the higher affinity of the nanofibres for PM2.5 and thus the PM2.5 capture increases for polyacrylonitrile/diethyl ammonium dihydrogen phosphate nanofibre in comparison with polyacrylonitrile nanofibrous membranes [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Natural fiber has good mechanical, physical, and chemical properties. [16,17] Kevlar has now replaced asbestos and has excellent braking properties, but research has shown its negative impact. The use of asbestos started by keeping its advantage of excellent braking properties, although further research has found that it leads to various kinds of cancer and causes serious lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have a lot of good properties with which we can replace synthetic materials. [1][2][3][4] Natural fiber use is increasing day by day in the development of new composites due to their excellent properties. [5][6][7] The recent synthetic fiber has been examined and shown to have many environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17,22] On the other hand, natural fibers are lightweight and easy to form and are less expensive, environmentally benign, and biodegradable. [1][2][3][4][5][6][7]16,17,[21][22][23][24] It also has a high specific strength and good tensile strength. [17,21,22] Natural fibers are used in many applications, such as plastering, building, construction, transportation, and so forth.…”
Section: Introductionmentioning
confidence: 99%